2020
DOI: 10.18488/journal.29.2020.72.255.267
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Impact of FDI, Export and Gross Domestic Savings on the Economic Growth in Bangladesh

Abstract: Contribution/Originality: This study contributes to the existing literature by showing the empirical contribution of Export, FDI, Gross Domestic Savings, inflation, industry value-added, and population growth on the Economic Growth in Bangladesh using ARDL ECM approach and also be beneficial for policymakers to take necessary steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…models. This finding is in line with the previous studies that found evidence of positive long run impact of domestic savings on economic growth (Gatsi & Appiah 2020;Joshi et al 2019;Miah & Majumder 2020;Ribaj & Mexhuani 2021). Also, the results show that investment as proxied by GFCF has negative long run impact on economic growth, while TRADE promotes economic growth in the long run.…”
Section: Analysis Of Panel Regression Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…models. This finding is in line with the previous studies that found evidence of positive long run impact of domestic savings on economic growth (Gatsi & Appiah 2020;Joshi et al 2019;Miah & Majumder 2020;Ribaj & Mexhuani 2021). Also, the results show that investment as proxied by GFCF has negative long run impact on economic growth, while TRADE promotes economic growth in the long run.…”
Section: Analysis Of Panel Regression Resultssupporting
confidence: 92%
“…The third group of studies consists of those that found insignificant or mixed results regarding the effect of savings on growth (Joshi, Pradhan & Bist 2019;Miah & Majumder 2020;Patra et al 2017;Yadav, Goyani & Mishra 2018). Among this group of studies, Bolarinwa and Obembe (2017) focussed on six African countries and found that saving had negative impact on growth in Burkina Faso and Niger, but positive impact for Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%